Unconventional Dying of Cotton Fabric using Chitosan-Functionalized Reactive dye - Shibraen, Mahmoud H. M. A.; elhadad, Shimaa s. m.; Hassan, Elwathig A. M.; Abdalnoor, Osman A. M.; Abdelwafa, Mohamed Awad; Asad, Rabie A. M. (Gezira Journal of Engineering and Applied Sciences, 2023)
Reducing the use of exhausting agents conventional dyeing process of cotton fabric with reactive dyes is essential to diminishing the tremendous influence of dyes released in wastewater on the environment. However, it remains a significant challenge to achieve both excellent dyeing properties and a low risk of water pollution. In this study, to eliminate exhausting agents’ usage in the reactive dyeing of cellulose fabrics, an attempt was made to functionalize reactive dyes with chitosan and subsequently dye cotton fabrics. As result, due to the physical interaction between chitosan and dye, the cotton fabric dyed with reactive dye-functionalized chitosan improved by 15% and 6.14 % in color strength compared with conventional dyeing and unconventional dyeing of cationization cotton fabrics, respectively. on other hand the cotton fabric dyed with reactive dye-functionalized chitosan also showed better fastness properties including washing, rubbing and lighting fastness. Considering the good dyeing properties of the reactive dye-functionalized chitosan, this promising technique may pave the way for the salt-free dyeing of cotton.. Also study the effect of Ammi visnaga oil  on microorganisms.